Elasticity of single-crystalline graphite: Inelastic x-ray scattering study - Maultzsch, Janina; et al. (Physical Review B, 2007)
The five independent elastic moduli of single-crystalline graphite are determined using inelastic x-ray scattering. At room temperature the elastic moduli are, in units of GPa, C-11=1109, C-12=139, C-13=0, C-33=38.7, and C-44=4.95. Our experimental results are compared with predictions of ab initio calculations and previously reported incomplete and contradictory data sets. We obtain an upper limit of 1.1 TPa for the on-axis Young's modulus of homogeneous carbon nanotube, thus providing important constraints for further theoretical advances and quantitative input to model elasticity in graphite nanotubes.